Virus-Induced Gene Silencing Methods and Protocols - Becker, Annette; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Plants are amazing organisms to study, some are important sources for pharmaceuticals, and others can help to elucidate molecular mechanisms required for a plant’s development and its interactions with the biotic or abiotic environment. Functional genomics is vastly lagging behind the speed of genome sequencing as high-throughput gene function assays are difficult to design, specifically for non-model plants. Bioinformatics tools are useful for gene identification and annotation but are of limited value for predictions concerning gene functions as gene functions are uncovered best by experimental approaches. Virus-Induced-Gene-Silencing (VIGS) is an easy to use, fast, and reliable method to achieve down regulation of target gene expression. Virus-Induced Gene Silencing: Methods and Protocols provides detailed protocols for VIGS experiments in several plant species including model and non-model plants. Also included in this book are recently developed protocols for VIGS-derived microRNA production in the plant or protein over expression, as well as chapters devoted to summarizing the molecular mechanisms of VIGS action and the vector systems developed so far. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Virus-Induced Gene Silencing: Methods and Protocols serves as a valuable resource for researchers from diverse fields of plant biology interested in experimental approaches to analyzing gene functions.
Virus-Induced Gene Silencing (VIGS) in Plants – An Overview of Target Species and the Virus-Derived Vector Systems -- Rationale for Developing New Virus Vectors to Analyze Gene Function in Grasses Through Virus-Induced Gene Silencing -- Virus Induced Gene Silencing for Rice Using Agroinoculation -- Utilizing Virus Induced Gene Silencing for the Functional Characterization of Maize Genes During Infection with the Fungal Pathogen Ustilago maydis -- Analysis of Developmental Control Genes Using Virus Induced Gene Silencing -- Virus Induced Gene Silencing in the Rapid Cycling Columbine Aquilegia coerulea 'Origami' -- Virus-Induced Gene Silencing of the Alkaloid-Producing Basal Eudicot Model Plant Eschscholzia californica (California Poppy) -- Virus-Induced Gene Silencing Using Artificial miRNAs in Nicotiana benthamiana -- The Use of VIGS Technology to Study Plant-Herbivore Interactions -- Virus-Aided Gene Expression and Silencing Using TRV for Functional Analysis of Floral Scent-Related Genes -- Virus-Induced Gene Silencing in Soybean and Common Bean -- Functional Genomic Analysis of Cotton Genes with Agrobacterium-Mediated Virus-Induced Gene Silencing -- Highly Efficient Virus-Induced Gene Silencing in Apple and Soybean by Apple latent spherical virus vector and Biolistic Inoculation -- VIGS A Tool to Study Fruit Development in Solanum lycopersicum -- A Protocol for VIGS in Arabidopsis thaliana Using a "One-Step" TYMV-Derived Vector -- Virus-Induced Gene Silencing in Strawberry Fruit.
Keywords: Human genetics; Gene expression; Human Genetics; Gene Expression